Benefits and limitations of FNAC in thyroid diseases: our institutional experience - editor1, Mohammed Arif; H, Sunil (International Journal of Research in Medical Sciences, 2017)
Background: To assess sensitivity and specificity of FNAC as a preoperative diagnostic tool for thyroid pathology. Methods: Relevant clinical data (demographic- age, sex, place, occupation) including history was obtained from the patient. A detailed clinical examination was performed. All these patients were subjected to various investigations which include thyroid function test and FNAC. Then the patients were subjected to routine line of management and followed up. The main component of this study FNAC was performed as per prescribed standard technique; these findings were then correlated with histopathological diagnosis. Results: Out of 150 patients, Eighty eight percent of the patients (132 cases) in our study were females and the rest 12% of the patients were males (18 cases). 72.73% of the females had benign swellings and 27.27% had malignant tumours of thyroid gland whereas 61.11% of male patients in our study had benign swellings and 38.89 % had malignant tumours of thyroid gland. The sensitivity and specificity of FNAC were 84.48%and 78.26%respectively. The positive and negative predictive values were 90.74%and 66.67% respectively. Conclusion: FNAC is safe, simple with economical and cost effective procedure. It gives a reliable pre-operative cytological diagnosis based on which surgical procedures can be confidently executed. An attempt is made hereby to compare our results with worldwide documented literature. The primary purpose is to avoid the false negative cytological reports in thyroid carcinoma as negative report gives a clinician a false sense of security that is harmful in the interest of both the patient and surgeon.